School Health Program: mental health action with high school students – experience report (Research, Society and Development, 2023)
Objective: The present study aims to expose the experience of medical students with an educational action explaining and discussing mental health and valuing the lives of students in the pre-university entrance exam on a dynamic monitored based on the School Health Program (PSE). This program focus to establish a partnership between the school community and primary care. Methodology: This study is characterized as an experience report of the realization of a dynamic by a group of medical students, approaching the theme of anxiety that precedes the entrance exam and the appreciation of life. Results: There was a high prevalence of students with symptoms of anxiety related to the entrance exam and lack of knowledge on how to seek help, such as the Centro de Valorização da Vida (CVV) and the health professionals that make up the Mental Health network. The difference between normal and pathological anxiety was also observed. Conclusion: It is concluded that there is an index of emotional instability in pre-university students, since most identified themselves with bad feelings during an activity. Furthermore, it was noted the need to extend the PSE to teaching, since anxiety also affects them, mainly due to the high level of daily stress.